PERLINDUNGAN HUKUM BAGI KORBAN DAN PEMBERIAN SANKSI PIDANA BAGI PELAKU HATE SPEECH PADA MASA PEMILU DI INDONESIA - Zakki Mubarok; Khamarudhin Syahrul Jihad (Universitas Karya Husada Semarang, 2024)
Law enforcement and the public are increasingly paying attention to the rise of hate speech in public life during the election season. Hate speech that targets individuals based on culture, ethnicity, race, religion, disability, sexual orientation, gender, skin color, nationality, or other characteristics can lead to hatred, provocation, incitement, violence, and even national division in the election season. Speech that encourages hate can create tension in society and lead to acts of discrimination, violence and/or death if it is not handled effectively, immediately and in accordance with the law. The author raises two issues regarding hate speech in response to its increasingly detrimental impact on victims: the need for criminal punishment for perpetrators of hate speech and legal protection for victims of hate speech. After analyzing research materials, this research uses a normative writing methodology and approaches legislative issues related to hate speech. The findings of this research provide legal protection to victims of hate speech which can give them a sense of security and protect individuals who are also targets of hate speech. Speech that encourages hatred is considered a criminal offense because every person who, whether intentionally or unintentionally, commits an unlawful act is required by the relevant law to be responsible for his or her actions and is considered guilty of an act that is punishable by imprisonment or a fine.